شعرچی یے: What is Poetry? - Dad, A.R (Hanken, 2013)
Less has been written about the critical study of the lyric in the Balochi literature. Different lyric writers have defined it as in a diverse way. In the article, it will be pointed out that what is a lyric and what are the primordial needs to analyze the lyric. This paper examines all the critical aspects of the lyric that how it is emerging as a poetic genre in the Balochi literature.